Peran Pengembangan Pariwisata Berkelanjutan dan Sentra kuliner Terhadap Pendapatan Masyarakat - Achmad Taufiq (Universitas Yudharta Pasuruan, 2023)
English Version This study aims to examine the effect of culinary businesses and sustainable tourism partially and simultaneously on community income in Surabaya City. In this context, the research method used is quantitative method, which allows researchers to collect data in the form of numbers and test the relationship between the variables studied. The data collection process was carried out by filling out a questionnaire by respondents who were selected incidentally (incidental sampling), namely taking a sample of people who were easily accessible or available at the time of the research. The number of respondents used was 40 people. The data analysis technique carried out includes several stages. First, the validity test and reliability test were carried out to ensure that the questionnaire instrument used was the right tool to measure the research variables and provide consistent results. Furthermore, the normality test, heteroscedasticity test, and multicollinearity test were used to check whether the data used met the statistical assumptions required in linear regression analysis. The multiple linear regression test results yielded the following conclusions: First, culinary business does not significantly affect the income of people around Surabaya City area. Second, sustainable tourism has a significant effect on community income around Surabaya City area. Finally, the F test results show that the combination of culinary businesses and sustainable tourism has a significant effect on community income in Surabaya City. This means that the development of these two sectors together has a positive impact on community income. Versi IndonesiaPenelitian ini bertujuan menginvestigasi dampak usaha kuliner dan pariwisata berkelanjutan, terhadap pendapatan masyarakat di Kota Surabaya. metodologi penelitian kuantitatif digunakan karena memungkinkan pengumpulan data berupa angka-angka dan analisis hubungan antara variabel-variabel yang sedang diteliti. Kuesioner disebarkan secara langsung pada respunden dengan metode sampel insidental, yaitu dengan memilih individu yang mudah diakses atau tersedia selama periode penelitian. Sebanyak 40 responden terlibat dalam penelitian ini. Hasil dari analisis regresi linier berganda mengarah pada kesimpulan berikut: Pertama, ditemukan bahwa usaha kuliner tidak memiliki pengaruh signifikan terhadap pendapatan penduduk di sekitar Kota Surabaya. Kedua, pariwisata berkelanjutan ternyata memiliki dampak yang signifikan terhadap pendapatan masyarakat lokal di wilayah Kota Surabaya. Terakhir, hasil uji F menunjukkan bahwa pengaruh gabungan dari usaha kuliner dan pariwisata berkelanjutan memiliki dampak yang signifikan terhadap pendapatan masyarakat di Kota Surabaya. Hal ini mengindikasikan bahwa pengembangan kedua sektor ini secara bersama-sama memiliki efek positif terhadap pendapatan masyarakat.